Análisis del Desempeño entre MONGODB Y COUCHDB Utilizando Norma ISO/IEC 25000. Caso Práctico: Aplicación Web de Gestión de Documentos CONAGOPARE Chimborazo - Unach (2019)
The main objective of this research project was to analyze the performance between the NoSQL(MongoDB and CouchDB) databases using the ISO/IEC 25010 standard, through which the parameters to evaluate the efficiency of the NoSQL databases were established, determining the base point to implement in the CONAGOPARE CHIMBORAZO DOCUMENT MANAGEMENT WEB APPLICATION, in order to offer a quality web application. After evaluating the two databases, it was found that MongoDB was slightly higher tan CouchDB. This work has a quantitative approach and through an experimental research provides a working environment to evaluate the perfomance of NoSQL databases. As a result of the research it was found that the NoSQL databases have better performance when managing large volumes of data. Formerly, the information of the documents in CONAGOPARE Chimborazo were stored in folders that used physical spaces but through this investagation the optimal NoSQL database was determined to be implemented in the Web application of GESTION DOCUMENTAL CONAGOPARE CHIMBORAZO. Fort he development of the web application the XP methodology was used, because it seems to be flexible to constant changes during its development, with the client feedback and the developer,